Pengaruh Good Corporate Governance, Konservatisme Akuntansi, dan Ukuran Perusahaan Terhadap Manajemen Laba (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Widia, Sri; Dina Adawiyah; Sri Yuli Ayu Putri (Fakultas Ekonomi, Universitas Ekasakti, 2024)
The purpose of this study is to see an estimate of earnings management practices in financial reporting, by analyzing the influence of good corporate governance, accounting conservatism, and company size on earnings management. The population is manufacturing companies listed on the IDX in 2018 – 2020. The sample was taken using a purposive sampling method and a total of 22 companies were obtained, resulting in a total of 66 units of analysis. The instruments used in testing the SPSS-assisted hypothesis, the hypothesis test using the coefficient of determination, t test and F test, and the method of analysis is multiple linear regression analysis, classical assumption test and descriptive statistical analysis. The results prove that GCG and accounting conservatism partially have a significant effect on earnings management, while company size individually does not have a significant effect on earnings management. The results of the F test show that simultaneously GCG, accounting conservatism and company size have a significant influence on earnings management.